The FAPI-FDG Mismatch: Unmasking an Occult Pancreatic Lesion via Fibroblast Activation Imaging Amidst Negative Glucose Metabolism and Morphological Findings - Nur Rohmat Maulana Saepudin; Hendra Budiawan; Arifudin Achmad; Trias Nugrahadi; A Hussein S Kartamihardja (HM Publisher, 2026)
Background: Fibroblast activation protein inhibitor (FAPI) positron emission tomography (PET) has emerged as a promising modality for imaging the tumor microenvironment, specifically targeting cancer-associated fibroblasts (CAFs). While 18F-FDG targets glucose metabolism, 68Ga-FAPI targets stromal activation. Discrepancies between these modalities can offer unique insights into early pathogenesis. We report a rare case of incidental focal pancreatic uptake on 68Ga-FAPI PET/CT in a patient with prostate cancer, occurring in the absence of metabolic activity on 18F-FDG PET/CT or anatomical abnormalities on contrast-enhanced CT. Case presentation: A 75-year-old male with a history of acinar adenocarcinoma of the prostate (Gleason 7, post-TURP) underwent multimodal staging to evaluate for metastasis. 68Ga-PSMA PET/CT showed intermediate uptake in the prostate but no distant metastasis. Subsequent 68Ga-FAPI-04 PET/CT revealed a striking, intense focal uptake in the pancreatic body. Conversely, follow-up 18F-FDG PET/CT demonstrated physiological background uptake in the pancreas, and abdominal CT showed no pancreatic mass. Laboratory results indicated a slightly elevated CA 19-9 (45.6 U/mL). The findings present a diagnostic dilemma between early stromal-rich malignancy and focal inflammatory processes. Conclusion: This case highlights the FAPI-FDG Mismatch, suggesting that stromal remodeling may precede metabolic reprogramming and morphological changes in pancreatic lesions. 68Ga-FAPI PET/CT demonstrates superior sensitivity for detecting occult stromal activity, necessitating new diagnostic algorithms for incidentalomas in the era of stromal imaging.